TRANSACTION ALERT DALAM MEMBERIKAN PERLINDUNGAN HUKUM BAGI NASABAH - Muhammad Kusriadhi, - (2019)
Increasingly advanced technological developments also cover the field of financial technology. Card Using Payment (APMK) is one form of technological development in the financial sector, in the implementation of APMK activities a more detailed arrangement is needed regarding the fulfillment of the security and reliability aspects of the banking system. Bank Indonesia issued a regulation on Transaction Alerts in order to increase the security of transactions in Payment Instruments using Cards. This study uses a normative juridical research method. This study was conducted to find out how Transaction Alert is implemented in Indonesia and how the bank's role in protecting customers from legal losses and protection must be taken by customers in resolving disputes in the event of negligence in implementing Indonesian bank regulations about Transaction Alerts. The result is a Bank Indonesia Regulation and a Bank Indonesia Circular Letter which regulates the Implementation of Payment Instruments Using Cards and how the regulations regarding the responsibilities of the organizers in carrying out Transaction Alerts regulated in legislation should be carried out